Active decompression and distraction sugosteogenesis for the treatment of calcifying odontogenic cyst (2020)
The calcifying odontogenic cyst is as a benign, rare developmental odontogenic cyst with a wide range of histologic characteristics. It may present along with other odontogenic pathologies such as odontoma, ameloblastoma, adenomatoid odontogenic tumor, ameloblastic fibroma, and ameloblastic fibro-odontoma. Clinically, it can be an either intra- or extraosseous painless swelling that can produce cortical expansion. It affects mostly the anterior area of the mandible. Radiographically, it appears as a well-circumscribed unilocular radiolucency containing flecks of indistinct radiopacities. In about one third of cases, an impacted tooth is associated. In this paper, we employ a patient with an enormous calcifying odontogenic cyst to review both the pathology and active decompression and distraction sugosteogenesis, a novel technique employed to treat odontogenic entities. This dual approach usually results in an accelerated bone healing (sugosteogenesis), partial removal of the cystic epithelium, thickening of the wall, and migration of chronic inflammatory cells which triggered epithelial modulation, ultimately causing a realignment in the biologic behavior of the lesion.